2020
DOI: 10.1002/aoc.5548
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic retrievable Ag/AgBr/ZnFe2O4 photocatalyst for efficient removal of organic pollutant under visible light

Abstract: In the present work, a visible‐light‐driven Ag/AgBr/ZnFe2O4 photocatalyst has been successfully synthesized via a deposition–precipitation and photoreduction method. The crystal structure, chemical composition, morphology and optical properties of the as‐prepared nanocomposites were characterized by X‐ray diffraction spectroscopy, X‐ray photoelectron spectroscopy, scanning electron microscopy, high‐resolution transmission electron microscopy, energy‐dispersive X‐ray spectroscope, UV–vis diffuse reflectance spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The photocatalytic enhancement observed in a Ag/ZnFe 2 O 4 nanocomposite can be attributed to electron storage in the Fermi energy of the Ag nanoparticles, as shown in Figure 8a [70]. However, in the case of Ag/AgBr/ZnFe 2 O 4 (Figure 8b) [155], photoexcited electrons from the ferrite as well as plasmon-excited electrons from the Ag nanoparticles are transferred to the CB of AgBr, resulting in efficient generation of photocatalytic active species. As for the magnetic properties of magnetic silver-integrated composites specifically, the ease of separation and recovery of the composite photocatalyst from the treated solution is often reported [20,63,153,160].…”
Section: Photocatalyst (Concentration Inmentioning
confidence: 98%
“…The photocatalytic enhancement observed in a Ag/ZnFe 2 O 4 nanocomposite can be attributed to electron storage in the Fermi energy of the Ag nanoparticles, as shown in Figure 8a [70]. However, in the case of Ag/AgBr/ZnFe 2 O 4 (Figure 8b) [155], photoexcited electrons from the ferrite as well as plasmon-excited electrons from the Ag nanoparticles are transferred to the CB of AgBr, resulting in efficient generation of photocatalytic active species. As for the magnetic properties of magnetic silver-integrated composites specifically, the ease of separation and recovery of the composite photocatalyst from the treated solution is often reported [20,63,153,160].…”
Section: Photocatalyst (Concentration Inmentioning
confidence: 98%
“…It was found that co-doped zinc ferrite (Zn 0.50 Cu 0.50 Fe 1.90 Bi 0.10 O 4 and Zn 0.50 Cu 0.50 Fe 1.95 Ce 0.05 O 4 ) nanoparticles exhibited a higher bisphenol A removal efficiency than the doped and un-doped zinc ferrite nanoparticles. Li et al [18] successfully synthesized a visible-light-driven Ag/AgBr/ZnFe 2 O 4 photocatalyst via a deposition-precipitation and photoreduction method. The prepared Ag/AgBr/ZnFe 2 O 4 nanocomposites exhibited high photocatalytic activities for the degradation of gaseous toluene and MO.…”
Section: Introductionmentioning
confidence: 99%